Awareness of cultural practices by skilled birth attendants during pregnancy and birth in Kenya: An interpretive phenomenological study - Teckla Kemboi Ngotie; Doreen KM Kaura; Bob Mash (Elsevier, 2022)
Cultural capacity among SBAs is recommended in maternal care to promote culturally safe care and meet the childbearing women's cultural needs and expectations. This study aimed to explore awareness of cultural practices by skilled birth during pregnancy and birth within the Keiyo community in Kenya. Methods: A qualitative phenomenological study was conducted between August to December 2019. A semi-structured interview guide was piloted with two SBAs. Individual interviews and data analysis were conducted iteratively. Eleven participants were interviewed, and saturation of themes was achieved after the ninth SBA. Audio recorded data were transcribed and analysed using ATLAS.ti Software version 8.4.4 (1135) that followed Van Manen's five steps of thematic analysis. Findings: The three themes that emerged from an inductive and iterative data analysis process were SBAs familiarity with cultural practices, SBAs awareness of cultural practices, women's expectations of clinical care and challenges to establishing a more collaborative relationship between SBAs, traditional birth attendants (TBAs) and childbearing women. Conclusion: The SBAs awareness of cultural practices was highlighted through relationships formed during care engagements. This awareness revealed a potential indicator for women's choice of caregiver. Awareness of threats to cultural safety and fear of disclosure potentially created mechanisms to promote more collaborative care. A broader scope of skilled care approaches requires heightening maternity care providers' cultural sensitisation to reduce gaps in women's cultural needs and expectations.